Pengaruh Perendaman Gigi di dalam Ekstrak Bonggol Nanas Terhadap Kekerasan Enamel Gigi secara Invitro - Deli Mona (Majalah Kedokteran Andalas, 2023)
A high level of acidity can cause demineralization in tooth enamel. Continuous exposure to acid will decrease hardness of tooth enamel. One of foods that contain acid is pineapple fruit. The purpose of this study is to examine the enamel hardness before and after submersion in pineapple tubercle extract (in vitro). The method of this study used laboratory experimental method with pre test - post test with control group design. Sample of 36 post-extraction premolar teeth were divided into treatment group using pineapple tubercle extract and control group using artificial saliva. Samples were immersed for 12 hours at 37º C using an incubator.  The results showed that the mean value of enamel surface hardness in treatment group decreased from 242 VHN to 231 VHN after immersion with pineapple tubercle extract and there was no significant difference in hardness in the control group. The results of unpaired T-test analysis showed a value of p <0.005, thus there were significant differences between the two groups. The conclusion of this study is that there is a significant decrease in hardness through submersion in pineapple tubercle extract to decrease the hardness of enamel surface.